Strategi Kompetitif Untuk Meningkatkan Minat Pengguna Bus Batik Solo Trans Kota Surakarta - Sitorus, Budi; Arifin, Dahlan; Septi Rahayu, Diana; Apriyatno, Chandra (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2024)
The role of public transport as a community choice in mobility is determined by public interest, it is the Government's goal to make people switch from private vehicles to public transport to continue to be improved. Surakarta City has 2 (two) adequate transportation nodes with Tirtonadi Terminal and Solo Balapan Station which are now integrated with a connecting bridge to facilitate the community to travel. Batik Solo Trans Surakarta is a feeder transport service that serves 6 (six) corridors in 2020 which are determined through the Decree of the Mayor of Surakarta. The Batik Solo Trans bus model is ¾-shaped and can carry 20 passengers, with facilities for passengers with disabilities, the elderly, pregnant women and mothers carrying children. Every year the number of Batik Trans Bus service corridors increases but inversely proportional to the occupancy rate of the number of passengers decreases, therefore a competitive strategy is needed with on line transportation that already exists in the community. Based on the results of previous research, it was found that the decline in user interest in Batik Solo Trans Bus was caused by the lack of optimal service of Batik Solo Trans Bus in Surakarta City and the decline in people's purchasing power determined by ATP and WTP. The research objective is to analyse the strategy to increase the interest of public transport users in Surakarta City. The research method is to conduct a literature study technique with analysis using SWOT. Strengths and weaknesses are in terms of strengths, namely 1) The rate of economic growth is increasing; 2) The unemployment rate is decreasing, and the weaknesses are 1) Public transport users are declining; 2) Competition with online transport is increasing.